Electron transfer mechanism mediated nitrogen-enriched biochar encapsulated cobalt nanoparticles catalyst as an effective persulfate activator for doxycycline removal. (15th January 2023) - Jiang, Zijian; Wei, Jia; Zhang, Yifei; Niu, Xiruo; Li, Jiamei; Li, Yanan; Pan, Guoping; Xu, Mengdie; Cui, Xueru; Cui, Nan; Li, Jun
Abstract: To address the current water pollution issues, one of the most important technologies is the development of efficient and environmental-friendly catalysts for the treatment of organic pollutants in water. In this study, a nitrogen-enriched biochar encapsulated cobalt nanoparticles composite (Co@N-BC) was synthesized using a one-step pyrolysis method based on metal-organic frameworks (MOFs) and leaf biomass as precursors. The obtained Co@N-BC possessed more functional group, large specific surface area and less cobalt ion leaching, which were used for efficient persulfate (PS) activation for approximately 92.72% DOX (50 mg/L) removal in 30 min. The quenching test, electron paramagnetic resonance (EPR), and electrochemical characterization of the Co@N-BC/PS system revealed that electron transfer was the primary pathway for DOX elimination. Moreover, the Co@N-BC/PS system had satisfactory stability in a wide pH range (2–10) and was not adversely affected by the various anions or water matrix. This research will shed new light on the design and development of MOF derivatives, as well as provide technical support for the eradication of antibiotics. Graphical abstract: Image 1 Highlights: N-doped biochar wrapped cobalt nanoparticles composite was successfully synthesized. 8%-Co@N-BC-800 showed satisfactory catalytic properties in a wide range pH. The electron transfer was reckoned as the dominated pathway for DOX degradation. The removal mechanism and toxicity of degradative intermediates were studied.